Reductive Coupling Synthesis of a Soluble Poly(9,10-anthrylene ethynylene) - Isabell Geisler (Organic Materials, 2021)
Abstract A fully soluble poly(9,10-anthrylene ethynylene), poly[2,6-(2-octyldecyl)-9,10-anthrylene ethynylene] PAAE, with moderate degrees of polymerization Pn of ca. 10 is generated in a reductive, dehalogenative homocoupling scheme, starting from a 2,6-dialkylated 9,10-bis(dibromomethylene)-9,10-dihydroanthracene monomer and n-BuLi/CuCN as the reducing agent. PAAE shows surprisingly broad and unstructured absorption and photoluminescence emission bands with peaks at 506 nm and 611 nm, respectively, both in chloroform solution. The long absorption tail ranging into the 600–700 nm region and the large Stokes shift points to a high degree of geometrical disorder in the arrangement of the 9,10-anthrylene chromophores along the distorted polymer backbone. This disorder is borne out in the unusually strong wavelength dependence of fluorescence depolarisation, both with regards to the excitation and the emission wavelengths. Picosecond fluorescence depolarisation spectroscopy provides clear evidence for the presence of orthogonal transition dipole moments, presumably arising from the off-axis transition of the anthracene unit and the on-axis transition of the polymer backbone. Intramolecular energy relaxation then gives rise to the observed fluorescence depolarization dynamics.